High-performance computing for real-time spectral estimation - Madeira, M. M. (2015)
This paper presents two separate investigations into the real-time implementation of the modified covariance spectral estimator: one comparing performances on digital signal processors, the TMS320C40, and the recently released ADSP2016x (SHARC); another using application-specific custom circuitry. The advantages and disadvantages of each of these different approaches are reviewed, resulting in the design of a field-programmable gate array/digital signal processor-based high-performance system that combines the hardware and software approaches. In conjunction with pulsed Doppler ultrasound blood-flow detectors, the spectral estimator offers increased sensitivity in the non-invasive detection of arterial disease. (C) 1999 Elsevier Science Ltd. All rights reserved.